Dynamics of cell-fate determination and patterning in the vascular bundles of Arabidopsis thaliana - Benítez, Mariana; Hejátko, Jan (PLoS One, 2013)
Plant vascular meristems are sets of pluripotent cells that enable radial growth by giving rise to vascular tissues and are therefore crucial to plant development. However, the overall dynamics of cellular determination and patterning in and around vascular meristems is still unexplored. We study this process in the shoot vascular tissue of Arabidopsis thaliana, which is organized in vascular bundles that contain three basic cell types (procambium, xylem and phloem). A set of molecules involved in this process has now been identified and partially characterized, but it is not yet clear how the regulatory interactions among them, in conjunction with cellular communication processes, give rise to the steady patterns that accompany cell-fate determination and arrangement within vascular bundles. We put forward a dynamic model factoring in the interactions between molecules (genes, peptides, mRNA and hormones) that have been reported to be central in this process, as well as the relevant communication mechanisms. When a few proposed interactions (unverified, but based on related data) are postulated, the model reproduces the hormonal and molecular patterns expected for the three regions within vascular bundles. In order to test the model, we simulated mutant and hormone-depleted systems and compared the results with experimentally reported phenotypes. The proposed model provides a formal framework integrating a set of growing experimental data and renders a dynamic account of how the collective action of hormones, genes, and other molecules may result in the specification of the three main cell types within shoot vascular bundles. It also offers a tool to test the necessity and sufficiency of particular interactions and conditions for vascular patterning and yields novel predictions that may be experimentally tested. Finally, this model provides a reference for further studies comparing the overall dynamics of tissue organization and formation by meristems in other plant organs and species.
Keywords: Arabidopsis Proteins; Arabidopsis; Signal Transduction; Protein Kinases; proteinkinasy; cytokininy; Cell Differentiation; Computer Simulation; Models, Biological; signální transdukce; Algorithms; počítačová simulace; genové regulační sítě; biologické modely; algoritmy; Plant Vascular Bundle; Gene Expression Regulation, Plant; Meristem; meristém; Gene Regulatory Networks; regulace genové exprese u rostlin; Cytokinins; buněčná diferenciace; cévní svazky rostlin; proteiny huseníčku